Utilization of Digital Health Applications in Implementing the Dengue Vector Control Program - Sevilla Ukhtil Huvaid; Hasmiwati Hasmiwati; Nursyirwan Effendi; Yuniar Lestari; Afrizal Afrizal; Rizanda Machmud; Nuzulia Irawati; Delmi Sulastri (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
One house one larva monitor movement is a dengue vector control program of the Ministry of Health which has been promoted since 2016. However, there are still several areas that have not been successful in implementing this movement, one of which includes the City of Padang. The purpose of this study was to examine the importance of using digital applications in implementing dengue vector control programs. This research is a research with qualitative methods using the case study genre through a constructivist approach. The location of the qualitative research was carried out at the Padang City Health Office, in the working areas of the Nanggalo Health Center, Pagambiran Health Center, and Rawang Health Center which were designated as research areas. This research was conducted in 2023 with informants including the person in charge of the dengue fever program at the Padang City Health Service, the person in charge of the dengue fever program at the Community Health Center, and the larva monitoring coordinator. The results of the study indicate that efforts to control dengue vectors through the One House One larva monitor Movement are still not running as they should. This movement can only run when larva monitor performs its main tasks and functions in accordance with the provisions. For this reason, it is necessary to carry out coaching and supervision efforts. However, there are several obstacles that require the design of a comprehensive and integrated digital health application to improve the health information system to improve the performance of larva monitors. Keyword: Dengue Hemorrhagic Fever , Digital Health, Vector Dengue